Does AI increase cognitive abilities, decrease them, or a little bit of each? And what are its implications for identification and development of the gifted? - Sternberg, Robert J. (Frontiers in Education, 2026)
AI, and especially generative AI, may have an effect on the number of gifted people in the world. But whether this effect will be positive or negative is up to us, collectively, and to each individual. This essay opens with a consideration of possible effects of AI on the giftedness of a society taken as a whole. Then it presents a philosophical conundrum, that of the Chinese Room, that is relevant to assessing the effects of AI. Next it reviews some recent empirical literature relevant to the question of AI’s effects on cognition and cognitive gifts. Then it discusses these effects. Finally, it draws some conclusions, in particular, that whether AI increases or decreases giftedness in a society is not preordained, but rather reflects a choice.